Research on CFR algorithm for Internet - ZHANG Xin1; ZHAO Hai1; ZHANG Wen-bo2; LI Chao1 (Tongxin xuebao)
At first vast data were counted, then the small world and scale-free character in Internet was computed and analyzed. Based on those a new searching method for Internet resources was put forward –the connection first routing （CFR）. This method made the best use of the characters, which were the average shortest path between nodes and existing a few nodes with huge connection degree in Internet. So it could realize an efficient search for Internet resources. Finally by implementing Internet topology creator and conducting emulation experiments, the method was verified to be highly efficient, less time consumption and less network load.